Recent advances in the metal-organic framework-based electrocatalysts for trifunctional electrocatalysis - Devi, Bandhana; Koner, Rik Rani; Kurungot, Sreekumar (Dalton Transactions, 2022)
The sustainable energy technology is in great demand due to the depletion and the risks associated with the use of fossil fuels. Various energy technologies like regenerative fuel cells, zinc-air batteries, and overall water-splitting devices have a huge scope in the growth of green energy. The efficiency of these devices is reliant upon the multifunctional electrocatalysts, which include both bifunctional and trifunctional electrocatalysts. Among the different categories of the materials used for such multifunctional electrocatalysis, metal-organic-frameworks (MOFs) occupy a very consolidated place because of their high surface area, porosity, and many other unique physicochemical properties. However, the use of MOFs for the trifunctional electrocatalytic applications is in the budding phase and needs to be explored more. Further, most of these MOF-based trifunctional electrocatalysts are derived by pyrolyzing MOFs at high temperatures. Therefore, there is a need to develop more conductive MOFs which can be directly utilized for the trifunctional applications. In this frontier article, we present the latest reports on the MOF-based materials for trifunctional applications. The material design strategies of the MOF-based materials for trifunctional electrocatalysis have been discussed. The progressive improvements made with MOFs in electrocatalytic applications have been provided with emphasis on the structural, active site and compositional requirements. Finally, the challenges and viewpoints on the future development of the MOF-based materials for trifunctional electrocatalysis have been provided.